2017
DOI: 10.1002/2016jd026408
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of the climatological composition of the Asian summer monsoon anticyclone based on 10 years of Aura Microwave Limb Sounder measurements

Abstract: Intense deep convection associated with the Asian summer monsoon (ASM) lofts surface pollutants to the upper troposphere/lower stratosphere (UTLS), where strong winds and long chemical lifetimes allow intercontinental transport, affecting atmospheric composition around the globe. The Aura Microwave Limb Sounder (MLS), launched in 2004, makes simultaneous colocated measurements of trace gases and cloud ice water content (a proxy for deep convection) in the UTLS on a daily basis. Here we exploit the dense spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 177 publications
(425 reference statements)
8
126
0
Order By: Relevance
“…EMAC-simulated O 3 at different isentropic surfaces. Multi-annual monthly averages are calculated for the same period as in Santee et al (2017) and agree well with their figures (370 and 390 K). However, at the level corresponding to the HALO flight altitude (360 K), O 3 is enhanced in the ASMA in September (i) and the observed sudden increase at the southern ASMA edge over Oman is also reproduced (arrow).…”
Section: Datasupporting
confidence: 64%
See 2 more Smart Citations
“…EMAC-simulated O 3 at different isentropic surfaces. Multi-annual monthly averages are calculated for the same period as in Santee et al (2017) and agree well with their figures (370 and 390 K). However, at the level corresponding to the HALO flight altitude (360 K), O 3 is enhanced in the ASMA in September (i) and the observed sudden increase at the southern ASMA edge over Oman is also reproduced (arrow).…”
Section: Datasupporting
confidence: 64%
“…Ten-year averages of simulated O 3 reproduce the low-O 3 ASMA interior of satellite climatologies (Santee et al, 2017) as well as increased O 3 found by HALO ESMVal at slightly lower potential temperatures (Fig. 1).…”
Section: Datamentioning
confidence: 75%
See 1 more Smart Citation
“…Confinements of high concentrations of trace gases, including ozone precursors (e.g. hydrogen cyanide (HCN), CO, hydrochloric acid (HCl), NO x and PAN), and low ozone in the anticyclone are evident in satellite and aircraft observations (Randel et al, 2010;Vogel et al, 2014;Fadnavis et al, 2015;Ungermann et al, 2016;Santee et al, 2017). The observed ozone minimum is still an open question in spite of high amounts of its precursors in the anticyclone.…”
mentioning
confidence: 99%
“…Randel et al, 2010;Fadnavis et al, 2015;Santee et al, 2017). The uplifted air masses become confined into the anticyclone enclosed by jets (westerly and easterly jets to the north and south, respectively), which act as a strong transport barrier and restrict isentropic mixing into the extratropical lower stratosphere or the equatorial tropics (Ploeger et al, 2015.…”
mentioning
confidence: 99%